Fcc versus Non‐fcc Structural Isomerism of Gold Nanoparticles with Kernel Atom Packing Dependent Photoluminescence. (20th February 2019) - Zhuang, Shengli; Liao, Lingwen; Yuan, Jinyun; Xia, Nan; Zhao, Yan; Wang, Chengming; Gan, Zibao; Yan, Nan; He, Lizhong; Li, Jin; Deng, Haiteng; Guan, Zhaoyong; et al.
Abstract: Structural isomerism allows the correlation between structures and properties to be investigated. Unfortunately, the structural isomers of metal nanoparticles are rare and genuine structural isomerism with distinctly different kernel atom packing (e.g., face‐centered cubic (fcc) vs. non‐fcc) has not been reported until now. Herein we introduce a novel ion‐induction method to synthesize a unique gold nanocluster with a twist mirror symmetry structure. The as‐synthesized nanocluster has the same composition but different kernel atom packing to an existing gold nanocluster Au42 (TBBT)26 (TBBT=4‐tert‐butylbenzenethiolate). The fcc‐structured Au42 (TBBT)26 nanocluster shows more enhanced photoluminescence than the non‐fcc‐structured Au42 (TBBT)26 nanocluster, indicating that the fcc‐structure is more beneficial for emission than the non‐fcc structure. This idea was supported by comparison of the emission intensity of another three pairs of gold nanoclusters with similar compositions and sizes but with different kernel atom packings (fcc vs. non‐fcc). Abstract : Kerne und Wirkung : Eine Ioneninduktionsmethode ergibt einen einzigartigen Goldnanocluster mit verdrehter Spiegelsymmetriestruktur. Der Nanocluster zeigt die gleiche Zusammensetzung, jedoch eine unterschiedliche Packung der Kernatome (fcc vs. non‐fcc) wie ein existierender Gold‐Nanocluster Au42 (TBBT)26 (TBBT=4‐ tert ‐butylbenzolthiolat). Seine Photolumineszenzeigenschaften hängen von der Packung der Kernatome ab.